Food fraud detection in commercial pomegranate molasses syrups by UV–VIS spectroscopy, ATR-FTIR spectroscopy and HPLC methods. (August 2017) - El Darra, Nada; Rajha, Hiba N.; Saleh, Fatima; Al-Oweini, Rami; Maroun, Richard G.; Louka, Nicolas
Abstract: Food fraud is a serious ethical and economic problem affecting the food industry everywhere. As pomegranate molasses' consumption continues to increase due to its unique taste and antioxidant activity, its adulteration is taking several forms. Customers are deluded by the "100% pomegranate content" label present on most of the commercial pomegranate molasses. The purpose of this study was to detect, for the first time, the adulteration of commercial pomegranate molasses with date molasses. To distinguish pomegranate molasses from the date syrup, we determined different parameters that could signal adulteration, such as total acidity content, polyphenol yield, anthocyanins concentration, colour intensity and antiradical activity. UV–VIS spectroscopy was used as a screening method to detect fraud and High Performance Liquid Chromatography (HPLC) was conducted for a quantitative analysis. Additionally, Attenuated Total Reflectance Fourier-Transform Infrared (ATR-FTIR) spectroscopic analysis was conducted to compare the resulting spectra of commercial pomegranate molasses, natural pomegranate molasses and date syrup. Our findings support the hypothesis that some of the commercialized pomegranate molasses in the Middle East area are adulterated with cheaper date syrup. Highlights: Some commercial pomegranate molasses could be adulterated by date syrup. Phenolic content is a basic criterion for authentifying pomegranate molasses. UV–VIS spectroscopy is proposed to detect adulteration of pomegranate molasses. ATR-FTIR and HPLC confirm the authenticity of pomegranate molasses.